2011
DOI: 10.1016/j.rmed.2011.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The estimated pulmonary artery pressure can be elevated in Behçet’s syndrome

Abstract: When BS involves the pulmonary arteries, it can cause mild elevations in the estimated sPAP, decrease in DL(CO), mild cardiac dysfunction and increase in pro-BNP levels. These findings suggest that BS can also affect the small/micro vessels of the heart and the lungs in addition to the well-recognized large vessel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Hemoptysis due to pulmonary arterial aneurysms (PAA) should be differentiated from pulmonary emboli. Anticoagulant and fibrinolytic treatments given, based on a presumption of pulmonary emboli, may result in the death of patients with aneurysms (36). The diagnosis is confirmed by pulmonary angiography and CT.…”
Section: Prognosismentioning
confidence: 99%
“…Hemoptysis due to pulmonary arterial aneurysms (PAA) should be differentiated from pulmonary emboli. Anticoagulant and fibrinolytic treatments given, based on a presumption of pulmonary emboli, may result in the death of patients with aneurysms (36). The diagnosis is confirmed by pulmonary angiography and CT.…”
Section: Prognosismentioning
confidence: 99%
“…In our study, we found that the levels of BNP, Cr, CRP, hsCRP were signi cantly higher in the valvular involvement group than in the non-valvular involvement group. Previous studies suggested that the elevated level of BNP in BD patients was associated with the heart strain and elevated risk of cardiac pump problems [18,19]. The serum Cr level was an independent predictor for heart failure hospitalizations [20].…”
Section: Discussionmentioning
confidence: 86%
“…In a controlled study among BS patients with and without pulmonary vascular disease, healthy controls, and patients with scleroderma included as diseased controls, we found out that close to 1/5 of BS patients had mildly (35-45 mmHg) elevated systolic pulmonary artery pressure (10). In addition, as in systemic sclerosis, some patients had impaired lung diffusion capacity and mild disturbances of cardiac function suggesting small vessel disease in these patients as well.…”
Section: Pulmonary Artery Hypertensionmentioning
confidence: 80%